Deep brain stimulation: practical insights and common queries. Issue 6 (29th July 2019) - Baig, Fahd; Robb, Thomas; Mooney, Lucy; Robbins, Caroline; Norris, Caroline; Barua, Neil; Szewczyk-Krolikowski, Konrad; Whone, Alan
Abstract : The number of patients with deep brain stimulation (DBS) devices implanted is increasing. Although practices vary between centres, patients are typically given training and information from their DBS nurse or clinician, as well as a comprehensive device manual and contact details for their device manufacturer. However, for the lifetime of a patient with a DBS system, most of their secondary care often occurs in a centre without a co-located DBS service. The local neurologist is often asked pragmatic questions regarding the do's and don'ts for patients with DBS systems. While a DBS centre or device manufacturer can provide advice, we thought that it will be helpful to outline the overall management of DBS for movement disorders and the approach to commonly raised questions. We describe briefly the clinical application of DBS and discuss common scenarios where there are possible compatibility issues around the device.